2017
DOI: 10.3386/w23148
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Prescription Drug Monitoring Programs on Opioid Utilization in Medicare

Abstract: The misuse of prescription opioids has become a serious epidemic in the US. In response, states have implemented Prescription Drug Monitoring Programs (PDMPs), which record a patient's opioid prescribing history. While few providers participated in early systems, states have recently begun to require providers to access the PDMP under certain circumstances. We find that "must access" PDMPs significantly reduce measures of misuse in Medicare Part D. In contrast, we find that PDMPs without such provisions have n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
183
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(194 citation statements)
references
References 1 publication
9
183
2
Order By: Relevance
“…The non‐significant findings were also reported in some previous studies , but not all . The research using most recent data sources, however, consistently suggested the program effectiveness in states that adopted best practices .…”
Section: Discussionmentioning
confidence: 46%
“…The non‐significant findings were also reported in some previous studies , but not all . The research using most recent data sources, however, consistently suggested the program effectiveness in states that adopted best practices .…”
Section: Discussionmentioning
confidence: 46%
“…We also included a set of variables that reflect the availability of health care services, and so access to prescription drugs: percent of the county population with no health insurance; and the number of active Medical Doctors per 1000 population. Since past research has indicated that state‐level “must‐access” electronic prescription drug monitoring programs have statistically significant effects on opioid use, we also include an indicator variable for that state policy . Finally, all models include year indicator variables and county fixed effects.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research has shown that adverse labor market conditions may contribute to higher disability rates (Black et al, 2002;Autor and Duggan, 2003;Erceg and Levin, 2014;Hall, 2015). Similarly, as chronic diagnosed pain is by itself grounds for disability, the direction of causation between opioid use and disability may run in either direction (GAO, 2011;Morden et al, 2014;Meara et al, 2016;Buchmueller and Carey, 2017;Song, 2017). 27…”
Section: Resultsmentioning
confidence: 99%